Immune regulation in pathophysiology and targeted therapy for itch in atopic dermatitis - Chih-Hung Lee (Wolters Kluwer Medknow Publications, 2016)
Itch is an unpleasant perception that provokes one to desire to scratch. It results from the activation of free nerve endings by noxious stimuli in the skin. Atopic dermatitis (AD) is a prototypic inflammatory skin disease that always occurs with an intense itch. AD involves many components of skin-associated lymphoid tissue (SALT). As a disease with polarized T helper 2 cell activation, AD involves eosinophil infiltration and immunoglobulin E, interleukin (IL)-2, IL-4, IL-13, and IL-31 production. As a disease involving an impaired skin barrier, AD is characterized by the enhanced transepidermal entry of allergens and the production of thymic stromal lymphopoietin (TSLP) from epidermal keratinocytes, which worsen atopic march and disease progression. Both immune and epidermal events interact with cutaneous nerve components, including transient receptor potential (TRP) channels and opioid receptors, causing both the perception and propagation of itch from the skin to the brain. In addition to treating itch through TRP channels and opioid receptors, it might be possible to target the various cellular components of SALT, including keratinocytes, eosinophils, and soluble factors, such as IL-31, IL-4, IL-13, IL-31, and TSLP.